2017
DOI: 10.1073/pnas.1705169114
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserves solve an important bycatch problem in fisheries

Abstract: Management of the diverse fisheries of the world has had mixed success. While managing single species in data-rich environments has been largely effective, perhaps the greatest challenge facing fishery managers is how to deal with mixed stocks of fish with a range of life histories that reside in the same location. Because many fishing gears are nonselective, and the costs of making gear selective can be high, a particular problem is bycatch of weak stocks. This problem is most severe when the weak stock is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 29 publications
4
77
0
Order By: Relevance
“…Where sustainable catch rates differ across species, leading to strong and weak stocks, MPAs may also benefit fisheries by reducing the cost of bycatch reduction (Hastings et al. ). Generally, economic benefits to fisheries are experienced as increased revenue per unit of fishing effort, or reduced effort and cost per unit of fish caught.…”
Section: The Market Benefits Of Marine Protected Areasmentioning
confidence: 99%
See 3 more Smart Citations
“…Where sustainable catch rates differ across species, leading to strong and weak stocks, MPAs may also benefit fisheries by reducing the cost of bycatch reduction (Hastings et al. ). Generally, economic benefits to fisheries are experienced as increased revenue per unit of fishing effort, or reduced effort and cost per unit of fish caught.…”
Section: The Market Benefits Of Marine Protected Areasmentioning
confidence: 99%
“…Whether MPAs provide benefits to fisheries will depend on a range of features, including (1) source-sink dynamics of the fish population, (2) size of an MPA relative to the home range of fish species (Ovando et al 2016), (3) geographic extent of the fish population, (4) status of the fishery prior to MPA implementation (Ovando et al 2016), and most importantly, (5) adequate management and enforcement. Where sustainable catch rates differ across species, leading to strong and weak stocks, MPAs may also benefit fisheries by reducing the cost of bycatch reduction (Hastings et al 2017). Generally, economic benefits to fisheries are experienced as increased revenue per unit of fishing effort, or reduced effort and cost per unit of fish caught.…”
Section: The Market Benefits Of Marine Protected Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the overlap, at least partial, between the distributions of many marine species and MPAs, numerous illegal human activities continue within these areas and impact their biodiversity. Recent studies have found that no‐take zones, such as Marine Reserves, are effective management tools, which can provide valuable conservation and socio‐economic benefits by preventing habitat destruction and reducing fishing pressure, thus allowing the biomass and diversity of these areas to increase (Baskett & Barnett, ; Evans & Russ, ; Hastings, Gaines, & Costello, ; Pichegru, Grémillet, Crawford, & Ryan, ).…”
Section: Introductionmentioning
confidence: 99%